ANALISIS PEMAHAMAN SISWA DALAM MENYELESAIKAN SOAL MATRIKS DITINJAU DARI SELF EFFICACYM MENYELESAIKAN SOAL MATRIKS DITINJAU DARI SELF EFFICACY - dewianggreini; Eko Priyojadmiko (Jurnal Padegogik, 2022)
Understanding ability is closely related to students' beliefs in understanding a subject matter. If students already understand the material, students will be sure or confident to work on the questions on the material provided or students can more easily continue to the next stage. The purpose of this study is to determine the understanding of students who have high, medium, and low self-efficacy. Data collection methods used are questionnaires, test questions and interviews. The instruments used are self-efficacy questionnaires, tests of student understanding and interview guidelines. Researchers took 6 research subjects, namely 2 students with high self-confidence, 2 students with moderate self-confidence and 2 students with low self-confidence. The presentation of the data carried out is to describe the results of students' understanding tests and the results of student interviews. The results showed that the high level of self-efficacy of students was able to meet all indicators of understanding. Students who have moderate self-efficacy are only able to fulfill 5 of the 7 indicators and can do 4 of the 5 questions given. For students who have low self-efficacy, they are only able to fulfill 5 of the 7 indicators and can only answer 3 of the 5 questions given